Tsunami Threat Assessment for the North and Central Pacific Coast of Costa Rica - Chacon-Barrantes, Silvia (2018)
Chacón-Barrantes, S. E., & Arozarena Llopis, I. (2018). Tsunami Threat Assessment for the North and Central Pacific Coast of Costa Rica. Abstract at 2018 Seismology of the Americas Meeting. Latin American and Caribbean Seismological Commission, Seismological Society of America. Seismological Research Letters, 89(2B), 814. https://doi.org/10.1785/0220180082